1997
DOI: 10.1046/j.1471-4159.1997.69041684.x
|View full text |Cite
|
Sign up to set email alerts
|

3‐Methoxytyramine Formation Following Monoamine Oxidase Inhibition Is a Poor Index of Dendritic Dopamine Release in the Substantia Nigra

Abstract: This study was undertaken, using microdialysis, to compare the extracellular concentration of 3-methoxytyramine and dopamine in dialysate from the striatum and substantia nigra, after pargyline (75 mg/kg), after pargyline plus amphetamine (3 mg/kg), and after pargyline plus reserpine (5 mg/kg) administration. Treatment with pargyline alone increased the extracellular dopamine concentration by 70% in the striatum and by 140% in the substantia nigra and induced in both regions a time-dependent accumulation of 3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…Pargyline inhibits MAO-catalysed DA metabolism (Planz et al 1972;Roth et al 1976;Waldmeier and Maitre 1976), thereby accumulating intraneuronal DA and increasing resting DA release (Butcher et al 1990;Di Chiara et al 1993;Elverfors et al 1997). This is further corroborated by the present data, showing a threefold increase in striatal extracellular DA levels in pargyline-treated animals.…”
Section: Discussionsupporting
confidence: 91%
“…Pargyline inhibits MAO-catalysed DA metabolism (Planz et al 1972;Roth et al 1976;Waldmeier and Maitre 1976), thereby accumulating intraneuronal DA and increasing resting DA release (Butcher et al 1990;Di Chiara et al 1993;Elverfors et al 1997). This is further corroborated by the present data, showing a threefold increase in striatal extracellular DA levels in pargyline-treated animals.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, numerous studies have been performed on the analysis of DA release in various experimental paradigms by assessing accumulation of 3-MT tissue levels in brain tissue, often after blockade of MAO by pargyline [7], [38]. However, while later in vivo microdialysis studies have generally confirmed the association between extracellular levels of DA and 3-MT [37], the static tissue measures of 3-MT accumulation have proven to be quite inaccurate measures of dynamics of DA release [39], [40].…”
Section: Discussionmentioning
confidence: 99%
“…Pleiomorphic vesicles have been detected in the symmetrical dendrodendritic synapses of SNc neurons (Groves and Linder, 1983) and have been shown more recently to express the vesicular monoamine transporter (Nirenberg et al, 1996). Vesicular storage of dopamine at the level of the SN is also supported by evidence that the nigral release of dopamine is sensitive to reserpine, a compound that depletes vesicular dopamine pools (Elverfors et al, 1997), as well as compounds that interfere with vesicular fusion and release (i.e., the 25 kDa synaptosome-associated protein SNAP-25; Bergquist et al, 2003). In addition, dendritic dopamine signaling can be terminated via the DAT as DAT blockade can enhance nigral dopamine levels (Robertson et al, 1991; Santiago and Westerink, 1992; Cragg et al, 1997; Cragg et al, 2001).…”
Section: Extrastriatal Actions Of Dopaminementioning
confidence: 93%